Urban Environmental Health in Bangladesh Slum: A Comparative Study of Two Metropolitan Cities - Hossain, MA; Moniruzzaman, M; Islam, MA (Journal of Science Foundation, 2013)
This study aims to present a comparative study of socioeconomic, physical and urban environmental health condition of two metropolitan cities in Bangladesh. Slums both from Khulna and Rajshahi city were selected for this study. Although both primary and secondary data were used, this study was mainly based on primary data gathered through household questionnaire survey. In order to determine the socio-economic, physical and environmental situations, only those who were the beneficiaries of the UNICEF project were interviewed. The study finds that poor socioeconomic status and inadequacy of urban services has had an immediate effect on urban health special the slum poor in metropolitan cities in the country. DOI: http://dx.doi.org/10.3329/jsf.v8i1-2.14628 J. Sci. Foundation, 8(1&2): 67-76, June-December 2010